2001
DOI: 10.1002/ijc.1228
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair gene polymorphisms, bulky DNA adducts in white blood cells and bladder cancer in a case-control study

Abstract: Individuals differ widely in their ability to repair DNA damage, and DNA-repair deficiency may be involved in modulating cancer risk. In a case-control study of 124 bladder-cancer patients and 85 hospital controls (urological and non-urological), 3 DNA polymorphisms localized in 3 genes of different repair pathways (XRCC1-Arg399Gln, exon 10; XRCC3-Thr241Met, exon 7; XPD-Lys751Gln, exon 23) have been analyzed. Results were correlated with DNA damage measured as 32 P-post-labeling bulky DNA adducts in white bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
151
4

Year Published

2001
2001
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 262 publications
(173 citation statements)
references
References 30 publications
(38 reference statements)
18
151
4
Order By: Relevance
“…11 A similar, although not statistically significant, effect was possibly suggested also for XRCC1, in agreement with the studies by Lunn et al 12 and Duell et al 16 A still weaker effect was shown for XRCC3-241 polymorphism for which, however, evidence of its possible involvement in DNAadducts repair has been provided. 18 Approximately two-thirds of our study subjects had at least a Gln variant at XPD-751 polymorphic locus, and tended to show higher levels of DNA adducts than subjects with 2 normal alleles. This difference was evident among traffic-exposed workers, suggesting a role for this polymorphism at higher levels of exposure.…”
Section: Multivariate Analysismentioning
confidence: 83%
See 3 more Smart Citations
“…11 A similar, although not statistically significant, effect was possibly suggested also for XRCC1, in agreement with the studies by Lunn et al 12 and Duell et al 16 A still weaker effect was shown for XRCC3-241 polymorphism for which, however, evidence of its possible involvement in DNAadducts repair has been provided. 18 Approximately two-thirds of our study subjects had at least a Gln variant at XPD-751 polymorphic locus, and tended to show higher levels of DNA adducts than subjects with 2 normal alleles. This difference was evident among traffic-exposed workers, suggesting a role for this polymorphism at higher levels of exposure.…”
Section: Multivariate Analysismentioning
confidence: 83%
“…PCR followed by enzymatic digestion was used for the genotyping of the XRCC1-Arg399Gln (G28152A, exon 10), XRCC3-Thr241Met (C18067T, exon 7) polymorphisms and XPD-Lys751Gln (A35931C, exon 23). 14,18 All of the PCR reactions were performed in a total reaction volume of 20 l containing 10 ng of genomic DNA, 0.4 units of Taq polymerase (PE applied biosystems) in PCR buffer 1ϫ, 1.5 mM MgCl 2 , 50 mM dNTPs and 250 nM of each primer. Thermal cycling conditions were as follows: initial denaturation step at 95°C for 3 min, 35 cycles of PCR consisting of 95°C for 20 sec, 20 sec at the appropriate annealing temperature (55°C, 67°C and 60°C, respectively), 72°C for 20 sec and a final extension step at 72°C for 5 min.…”
Section: Blood Collection and Storagementioning
confidence: 99%
See 2 more Smart Citations
“…25 Although the functional relevance of this polymorphism is unknown, it was reported recently that the XRCC3 C18067T polymorphism is associated with risk for melanoma 26 and bladder cancer. 27 In our study, we hypothesized that genetic variant of XRCC3 may contribute to genetic susceptibility to SCCHN and therefore would occur at different frequencies in individuals with and without cancer. To test this hypothesis, we performed a hospital-based case-control study using a polymerase chain reaction (PCR)-single-strand conformation polymorphism (SSCP) assay to genotype the variant of XRCC3 in 367 patients with SCCHN and 354 cancer-free controls.…”
mentioning
confidence: 98%